Patterns everywhere - Perron, Lisa Varchol (2023)
"When you take the time to look, you'll find that nature is full of patterns. Lyrical, rhyming verse and stunning photographs introduce young readers to patterns throughout the natural world"--
Includes bibliographical references.
Ages 5-9
Grades 2-3
Keywords: Pattern perception -- Juvenile literature; Nature -- Juvenile literature